A study on the glycoside content of Euphorbia hirta - Florentino, Susan Barican; Concepcion. Adoracion B.; Fernando, Elena S. (Quezon City: College of Pharmacy, University of the Philippines, 1981.)
The study dealt with the extraction and isolation of glycosides from gatas-gatas, scientifally known as E. hirta L. (Family Euphorbiaceae). The TLC and column chromatography was utilized to determine effective solvent system for the glycosides content of the plant studied.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, 1981.
Keywords: Glycosides; Euphorbiaceae; Gatas-gatas.; Golandrina; Botobotones